Treatment of complex wounds with PVC prosthesis and autologous partial skin graft: Accelerated and low-cost third-intention healing protocol - Diego Ariel-de-Lima; Lana Lacerda de-Lima; Renata Clazzer; Kêilerte Renes Gurgel Paiva; Antônio Vicente Dias de-Andrade; Jorge Edson Pinheiro dos-Santos; João Firmino da Silva Neto (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Complex wounds are serious tegumentary injuries that are difficult to resolve with conventional dressings. This study aimed to describe a third-intention wound healing technique, reproducible and low cost, applicable to complex wounds, using polyvinyl chloride (PVC) prosthesis temporarily placed in the injured area to promote the protection and stimulate its “granulation,” followed by autologous partial-thickness skin grafting. Method: Consecutively, 20 patients with complex wounds resulting from external causes were selected and divided into 2 groups: A - patients who underwent the coverage technique with PVC prosthesis, followed by grafting, and B - patients submitted to the care of the dressing team, with daily changes until wound granulation, standard in our institution. Patients were evaluated regarding length of stay; costs; local pain; complications; the time until medical discharge; and patient satisfaction. Results: The length of hospital stay, its costs, and the time until medical discharge were shorter in group A (p<0.05). However, there was no statistically significant difference in local pain between techniques A and B. Conclusion: The technique using PVC prosthesis and graft has good efficacy for treating complex wounds, being reproducible and inexpensive.